Scanning Electron Microscopic Hair Shaft Analysis in Ectodermal Dysplasia Syndromes. Issue 6 (7th September 2015) - Hirano‐Ali, Stefanie A.; Reed, Ashley M.; Rowan, Brandon J.; Sorrells, Timothy; Williams, Judith V.; Pariser, David M.; Hood, Antoinette F.; Salkey, Kimberly
Abstract: Objectives: The objective of the current study was to catalog hair shaft abnormalities in individuals with ectodermal dysplasia (ED) syndromes using scanning electron microscopy (SEM) and to compare the findings with those in unaffected controls. This is the second of a two‐part study, the first of which used light microscopy as the modality and was previously published. Methods: Scanning electron microscopy was performed in a blinded manner on hair shafts from 65 subjects with seven types of ED syndromes and 41 unaffected control subjects. Assessment was performed along the length of the shaft and in cross section. Setting: Hair donations were collected at the 28th Annual National Family Conference held by the National Foundation for Ectodermal Dysplasia. Control subjects were recruited from a private dermatology practice and an academic children's hospital outpatient dermatology clinic. Results: SEM identified various pathologic hair shaft abnormalities in each type of ED and in control patients. When hairs with all types of ED were grouped together and compared with those of control patients, the difference in the presence of small diameter and shallow and deep grooves was statistically significant (p < 0.05). When the EDs were separated according to subtype, statistically significant findings were also seen. Conclusion: SEM is a possible adjuvant tool in the diagnosis of ED syndromes. There are significant differences, with high specificity, between the hairs of individuals with ED and those of control subjects and between subtypes.